The Europeanisation of Good Neighborly Relations and Regional Cooperation Criteria: A Comparison between Albania and North Macedonia - Geri PILACA (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene, 2023)
Good neighbourly relations and regional cooperation demand that all the bilateral relations of a country be stable and that all the disputes are to be resolved before the signing of the Accession Treaty. Considering that Albania and North Macedonia are two candidate countries which are found at the same stage of the EU Accession, and the weight that such criteria hold for these countries, it is necessary to provide an assessment of their preparation in this regard. The EU studies field provides for the use of Europeanisation literature to measure the fulfilment of the Accession criteria, one approach of which is measuring the policy adoption. For this purpose, Albania and North Macedonia were used as case studies to measure the progress of Europeanisation through the policy adaptation process as regarding Good neighbourly relations and regional cooperation during the period 2000-2019.